Prevalence and genotypes of GBV‐C and its associations with HIV infection among persons who inject drugs in Eastern Europe. Issue 4 (16th September 2016) - Jõgeda, Ene‐Ly; Huik, Kristi; Pauskar, Merit; Kallas, Eveli; Karki, Tõnis; Des Jarlais, Don; Uusküla, Anneli; Lutsar, Irja; Avi, Radko
Abstract : We aimed to determine the rate of GBV‐C viremia, seropositivity, and genotypes among people who inject drugs (PWID) and healthy volunteers in Estonia and to evaluate associations between GBV‐C and sociodemographic factors, intravenous drug use, co‐infections. The study included 345 Caucasian PWID and 118 healthy volunteers. The presence of GBV‐C RNA (viremia) was determined by reverse transcriptase‐nested PCR in 5′ long terminal repeat. PCR products were sequenced and genotyped by phylogenetic analysis. GBV‐C seropositivity was determined by ELISA. One third of PWID (114/345) and 6% (7/118) of healthy volunteers (OR = 7.8, 95% CI = 3.5–20.5, P < 0.001) were GBV‐C viremic. In PWID group, 79% of sequences belonged to subtype 2a, 19% to subtype 2b, and two remained unclassified. In healthy volunteers, six out of seven sequences belonged to subtype 2a and one to subtype 2b. We found HIV+ PWID to have two times increased odds of being GBV‐C viremic compared to HIV− PWID (62% vs. 38%; OR = 2.13, 95% CI = 1.34–3.36, P = 0.001). In addition, odds of being GBV‐C viremic decreased with increasing age (OR = 0.94, 95% CI = 0.90–0.98, P = 0.001). HIV positivity remained associated with GBV‐C viremia in multivariate analysis after adjustment for age (OR = 2.23, 95% CI = 1.39–3.58, P = 0.001). GBV‐C seropositivity was similar among PWID and healthy volunteers (2.3% vs. 1.7%, respectively; OR = 1.4, 95% CI =0.3–13.5, P = 1). In an Eastern European country we demonstrated that GBV‐C viremia is common among PWID, but uncommon among healthy volunteers, and GBV‐C seropositivity is infrequent among both groups. Similarly to other European countries and USA, GBV‐C 2a is the most common genotype in Estonia. J. Med. Virol. 89:632–638, 2017 . © 2016 Wiley Periodicals, Inc.